Venezuelan geckos (Gekkonidae, Phyllodactylidae, Sphaerodactylidae) in the collection of the Universidad de Concepción in Chile, with description of the type series of Gonatodes ligiae and Gonatodes petersi (Sphaerodactylidae) - Barrio-Amorós, Cesar L.; Ortíz, Juan C. (Zootaxa, 2016)
Herein we catalogue all geckos (Gekkonidae, Phyllodactylidae and Sphaerodactylidae) collected by Roberto Donoso-Barros in Venezuela between 1963 and 1964, deposited in the Universidad de Concepción in Chile. Donoso-Barros did not provide detailed descriptions of two species of Gonatodes named by him, despite both being valid species. We take the opportunity to do so and the type series of Gonatodes ligiae and G. petersi are described for the first time. We also present images in life of all species collected by Donoso-Barros in Venezuela.